Judicial Shift in Paternal Child Custody Based on The Best Interests Principle - Iyut Paputungan; Fence M. Wantu; Mohamad Taufiq Zulfikar Sarson (Nusantara: Journal of Law and Islamic Law, 2026)
This article analyzes the judicial shift in granting child custody to fathers within Indonesian Islamic family law. Although hadhanah doctrine generally prioritizes mothers for children who have not reached mumayyiz age, Decision Number 2/Pdt.G/2025/PA.Tlm shows a different judicial construction. This normative legal research uses statutory and case approaches to examine the tension between maternal presumption under the Compilation of Islamic Law and the best interests of the child principle under Indonesian marriage and child protection laws. The study argues that paternal custody is not a deviation from hadhanah, but a contextual application of child-centered adjudication. The judge considered the father’s actual caregiving capacity, the child’s welfare, and the mother’s absence of objection as relevant legal facts. This decision reflects progressive legal reasoning that moves custody determination from formal parental priority toward evidentiary assessment of protection, stability, and child development in post-divorce family disputes before Indonesian religious courts today more decisively.